2019
DOI: 10.1007/s10815-019-01616-5
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome sequencing of endometrium revealed alterations in mRNAs and lncRNAs after ovarian stimulation

Abstract: Research question Using RNA-sequencing analysis, we investigated the relationship between ovarian stimulation and endometrial transcriptome profiles during the window of implantation (WOI) to identify candidate predictive factors for the WOI and to optimize timing for embryo transfer. Methods Twelve women with normal basal hormone levels and regular ovulation were randomly assigned into three groups based on sampling time: late-proliferate phase (P group), and receptive phase in natural cycles (LH+7, N group) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…During the fresh embryo transfer scheme, the hyper-physiological levels of E 2 elevated the P 4 levels, which reduced endometrial receptivity (Wu et al, 2012). Li et al confirmed that in IVF/ICSI patients, the supra-physiological E 2 concentration in COH affected endometrial transcriptome profiles, resulting in a shift of the embryo transfer window via endometrial mRNA and lncRNA sequencing (Li et al, 2020). Other researchers found that there was not sufficient evidence to confirm or deny the effect of E 2 levels on clinical outcomes during the IVF/ICSI cycle on the day of hCG administration (Kosmas, Kolibianakis & Devroey, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…During the fresh embryo transfer scheme, the hyper-physiological levels of E 2 elevated the P 4 levels, which reduced endometrial receptivity (Wu et al, 2012). Li et al confirmed that in IVF/ICSI patients, the supra-physiological E 2 concentration in COH affected endometrial transcriptome profiles, resulting in a shift of the embryo transfer window via endometrial mRNA and lncRNA sequencing (Li et al, 2020). Other researchers found that there was not sufficient evidence to confirm or deny the effect of E 2 levels on clinical outcomes during the IVF/ICSI cycle on the day of hCG administration (Kosmas, Kolibianakis & Devroey, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Cycles were excluded if: (1) the E2 level on trigger day was unavailable; (2) there were abnormal karyotypes in either of the couple; (3) embryos were generated using frozen or donor gametes, oocytes in vitro maturation, or non‐ejaculated sperms; (4) two or more fertilization methods were applied in a cycle; (5) embryo biopsies; (6) women with the diagnosis of adenomyosis, leiomyomas, intrauterine adhesion, endometrial polyps, uterine malformation, and cervical excisions. A complete cycle refers to a fresh cycle and subsequent FET cycles when all embryos are used, or at least one live birth is achieved 5 . The cycles were divided into six groups according to the E2 level on trigger day 13 : <1000, 1000–2000, 2000–3000, 3000–4000, 4000–5000 and ≥5000 pg/mL 13 …”
Section: Methodsmentioning
confidence: 99%
“…Another lncRNA, ENST00000433673 , is expressed in epithelial and stromal endometrial cells to enhance the synthesis of ITGAL and ICAM1, two proteins required for the adhesion of the trophoblast to the endometrium [ 192 ]. LncRNAs have also been proposed as biomarkers of endometrial receptivity, such as LINC01060 and LINC01104 , whose specific functions remain to be elucidated [ 193 ].…”
Section: Non-coding Rnasmentioning
confidence: 99%